Algerian water Security and Strategy of its Realization - Frimeche , Malika (Journal of Human Sciences, 2020)
Algeria as a very huge Mediterranean country ( with more than 20Million KM 2 ) is characterized by a distinguished geographic and climatic diversity, and a remarkable disequilibrium in matter of population distribution and density , as well as a very important water and irrigation potentiality, found in internal and external basins that are related directly with Mediterranean sea, in addition to a very important quantity of desert’s groundwater . However, Algeria can be considered as a semi or arid country similar to lot of southern Mediterranean countries. So to face this water scarcity,and population’s increasing needs in this field , it is very necessary to elaborate an efficient water policy.